Perfil dos agentes etiológicos detectados em sintomáticos respiratórios durante o primeiro ano da pandemia de covid-19 - Varela, Fernanda Hammes (2022)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has brought unprecedented challenges for the scientific and lay community, but especially for public health policies. The imposition of social restrictions, circulation control, and the use of masks were focal points for the epidemiological changes of respiratory infections during this period. Objective: The aim was to describe the frequency of respiratory pathogens in patients with suspicious COVID-19 during the initial period of the pandemic in the year 2020, in two hospitals in southern Brazil. Methods: Inpatients and outpatients older than 2 months with signs and symptoms of acute COVID-19 (cough, fever or sore throat) were prospectively included in the study from May to November 2020, in two hospitals in Porto Alegre - RS, Brazil. All participants performed RT-PCR for SARS-CoV-2, Influenza, and Respiratory Syncytial Virus (RSV), and in addition to these agents, pediatric patients performed a real-time PCR panel that evaluated 20 respiratory pathogens (three bacteria and 17 viruses). Results: A total of 2011 participants were screened, of which 356 were excluded (215 refused to participate, 139 were ineligible, 2 withdrew consent). Of these 1655, 868 were included in Hospital Moinhos de Vento (649 adults, and 219 under 18 years), and 787 in Hospital Restinga Extremo Sul (566 adults, and 221 under 18 years). Of the 1655 participants included in the final sample, 1435 participants had a viable sample for panel assessment for RSV, Influenza A and B. Of the participants under 18 years of age included, 436 had a viable sample for assessment of the expanded viral-bacterial panel of 20 pathogens. SARS-CoV-2 and rhinovirus were the main pathogens identified. An important finding was the absence of RSV and Influenza virus during this period. Conclusion: The prevalence of most respiratory pathogens usually found in the autumn and winter seasons, such as Respiratory Syncytial Virus (RSV) and Influenza, was exceptionally low in the months of May to November 2020, a period of important restrictions and social distancing in response to the pandemic. While these viruses disappeared from circulation, rhinovirus and SARS-CoV-2 were the main agents detected. Another significant finding is that COVID-19 in symptomatic children was less associated with hospitalization than other respiratory infections in children under 18 years of age.